Impact of Toll-Like Receptor 2 and 9 Gene Polymorphisms on COVID-19: Susceptibility, Severity, and Thrombosis - Alhabibi AM; Hassan AS; Abd Elbaky NM; Eid HA; Khalifa MAAA; Wahab MA; Althoqapy AA; Abdou AE; Zakaria DM; Nassef EM; Kasim SA; Saleh OI; et al. (Dove Medical Press, 2023)
Alshaymaa M Alhabibi,1 Asmaa S Hassan,1 Nashwa Mohamed Abd Elbaky,1 Hoda Asaad Eid,2 Mohie Aldeen Abd Alzaher Khalifa,3 Maisa A Wahab,4 Azza Ali Althoqapy,5 Aml E Abdou,5 Doaa Mohammed Zakaria,6 Eman Mostafa Nassef,6 Sammar Ahmed Kasim,6 Ola I Saleh,7 Asmaa Abdelghany Elsheikh,8 Mahmoud Lotfy,9 Alaa Sayed10 1Departments of Clinical Pathology, Faculty of Medicine for Girls, Al-Azhar University, Cairo, Egypt; 2Chest Disease, Faculty of Medicine for Girls, Al-Azhar University, Cairo, Egypt; 3Department of Chest Disease, General Organization for Teaching Hospitals and institutes, Cairo, Egypt; 4Vascular Surgery, Faculty of Medicine for Girls, Al-Azhar University, Cairo, Egypt; 5Medical Microbiology and Immunology Department, Faculty of Medicine for Girls, Al-Azhar University, Cairo, Egypt; 6Internal Medicine, Faculty of Medicine for Girls, Al-Azhar University, Cairo, Egypt; 7Radio-Diagnosis, Faculty of Medicine for Girls, Al-Azhar University, Cairo, Egypt; 8Community and Occupational Medicine, Faculty of Medicine for Girls, Al-Azhar University, Cairo, Egypt; 9Molecular Biology Department, Genetic Engineering & Biotechnology Research Institute, University of Sadat City, Sadat City, Minufiya, Egypt; 10Hormones Department, Medical Research and Clinical Studies Institute, National Research Centre, Cairo, EgyptCorrespondence: Alshaymaa M Alhabibi, Tel +201002894075, Email alshaymaa.alhabibi@yahoo.comBackground: Toll-like receptors (TLRs) play an important role in activation of innate and adaptive immune responses.Aim: We aimed to detect the association between TLR2 rs5743708 G>A and TLR9 rs5743836 C>T variants and COVID-19 disease susceptibility, severity, and thrombosis by using neutrophil extracellular traps (NETs).Subjects and Methods: We included 100 adult COVID-19 patients as well as 100 age- and gender-matched normal controls. Participants were genotyped for TLR2 rs5743708 and TLR9 rs5743836. Citrullinated Histone (H3) was detected as an indicator of NETs.Results: The mutant (G/A and C/C) genotypes and (A and C) alleles of TLR2 rs5743708 and TLR9 rs5743836, respectively, have been significantly related to a higher risk of COVID-19 infection, representing a significant risk factor for the severity of COVID-19. There was no significant association between the two variants and citrullinated histone (H3).Conclusion: TLR2 rs5743708 and TLR9 rs5743836 variants have been significantly related to a higher risk and severity of COVID-19 infection but had no effect on thrombus formation.Keywords: coronavirus disease 2019, single-nucleotide polymorphism, toll-like receptor, high resolution-CT, susceptibility, severity